Iron-catalyzed asymmetric hydrosilylation of ketones1. Issue 24 (25th March 2015) - Zuo, Ziqing; Zhang, Lei; Leng, Xuebing; Huang, Zheng
<x xml:space="preserve">Abstract</x> Iron complexes of chiral iminopyridine-oxazoline (IPO) ligands effectively catalyze asymmetric hydrosilylation of aryl ketones.